Intraoperative navigation in robotically assisted compartmental surgery of uterine cancer by visualisation of embryologically derived lymphatic networks with indocyanine‐green (ICG). Issue 5 (21st January 2016) - Kimmig, Rainer; Aktas, Bahriye; Buderath, Paul; Rusch, Peter; Heubner, Martin
Abstract : Background and Objectives: To evaluate feasibility of intraoperative visualization of embryologically defined organ compartments and their drainage by ICG in uterine cancer. Methods: Total of 2.5 mg of ICG have been injected into cervix or corpus in uterine cancer patients immediately prior to surgery. Green fluorescence was intermittently detected during robotically assisted laparoscopic surgery (Firefly System®, Intuitve Surgical Inc.). Total of 36 patients with uterine cancer without macroscopically suspicious nodes were evaluated with respect to their compartmental lymphatic network, collecting lymphatic vessels, and the connection to the postponed lymph basins. Results: Müllerian (sub) compartment and transport of lymph fluid along the lymphatic collectors and connecting vessels to the postponed lymph basins could be visualized invariably in all patients. Cervix drained along the ligamentous and caudal part of vascular mesometria, whereas midcorporal and fundal drainage occurred along the upper part of vascular mesometria and along the mesonephric pathway along the ovarian vessels. Conclusions: Visualization of lymphatic network and downstream flow of lymphatic fluid to the postponed lymph basins by ICG is feasible; it can be used to navigate along compartment boarders for education, intraoperative orientation, and quality control. It seems to confirm the compartmental order of pelvic organ systems and postponed lymph basins. J. Surg. Oncol. 2016;113:554–559 . © 2016 Wiley Periodicals, Inc.